THE EFFECTIVENESS OF THE DEVELOPMENT OF TERRITORIES IN THE STATE REGIONAL SYSTEM POLITICIANS - Natallia Gavkalova; Ludmila Avedyan; Oleksandr Akimov; Liudmyla Akimova; Victoria Belyavtseva (Фінансово-кредитна діяльність: проблеми теорії та практики)
It was determined that the development of territories depends on the choice of strategy, tactics and implementation tools regional policy of the state. And therefore, at the current stage of global transformations, they are expedient and permanently improve, as current practice shows approaches to managing the development of domestic territories. Trends and prospects of development are studied in territorial units of Ukraine in terms of implementation of the chosen strategy and current state regulations and regional policy. The study of the problem was carried out thanks to the application of methods of comparison, abstraction, analysis and generalization, as well as tabular and graphical modelling. It was determined that the prospects for the development of territories primarily depend on the strategy and tactics implementation of the state regional policy, which should take into account the dynamism of socio-economic development, the rate of digitization of the economy and the level of innovation and technology regions of highly developed countries of the world, with which domestic regions are becoming more and more difficult to compete. A set of measures was proposed to optimize the processes of managing the development of territories, in particular, the creation of mechanisms for combating post-pandemic consequences, stimulating purchasing consumer demand at the local level, improvement of tax policy, creation of favourable conditions for improving the qualification level of employees, rationalization of the financial redistribution mechanism resources between different territories, as well as between regional and state budgets, dissemination of effective anti-corruption practices at the local level. Prospects for the creation of territorial ones have been determined by communities taking into account positive and negative factors to reveal strong and weaknesses in order to identify opportunities and threats to their development at the regional level levels using a SWOT analysis. Ways to improve regional policy are proposed.